A Fusion Protein between Streptavidin and the Endogenous TLR4 Ligand EDA Targets Biotinylated Antigens to Dendritic Cells and Induces T Cell Responses In Vivo. (5th September 2013) - Arribillaga, Laura; Durantez, Maika; Lozano, Teresa; Rudilla, Francesc; Rehberger, Federico; Casares, Noelia; Villanueva, Lorea; Martinez, Marta; Gorraiz, Marta; Borrás-Cuesta, Francisco; Sarobe, Pablo; Prieto, Jesús; et al.
Abstract : The development of tools for efficient targeting of antigens to antigen presenting cells is of great importance for vaccine development. We have previously shown that fusion proteins containing antigens fused to the extra domain A from fibronectin (EDA), an endogenous TLR4 ligand, which targets antigens to TLR4-expressing dendritic cells (DC), are highly immunogenic. To facilitate the procedure of joining EDA to any antigen of choice, we have prepared the fusion protein EDAvidin by linking EDA to the N terminus of streptavidin, allowing its conjugation with biotinylated antigens. We found that EDAvidin, as streptavidin, forms tetramers and binds biotin or biotinylated proteins with a K d 2.6 × 10 −14 mol/L. EDAvidin favours the uptake of biotinylated green fluorescent protein by DC. Moreover, EDAvidin retains the proinflammatory properties of EDA, inducing NF- κ β by TLR4-expressing cells, as well as the production of TNF- α by the human monocyte cell line THP1 and IL-12 by DC. More importantly, immunization of mice with EDAvidin conjugated with the biotinylated nonstructural NS3 protein from hepatitis C virus induces a strong anti-NS3 T cell immune response. These results open a new way to use the EDA-based delivery tool to target any antigen of choice to DC for vaccination against infectious diseases and cancer.